Community as stakeholder: exploring corporate social responsibility outcome in Malaysian community development. - Ismail, Maimunah; Alias, Siti Noormi; Mohd. Rasdi, Roziah (2012)
Community is a neglected stakeholder in terms of corporate social responsibility (CSR) research. This article exxplores the outcomes of CSR initiatives in community development in Malaysia. It aims to i) examine the profile of CSR providers including multinational corporations (MNCs) and local companies; ii) measure the understanding of the individuals involved in terms of the orientation of CSR according to economic,ethical,legal or philanthropic responsibilities; iii)identify the outcome of CSR practices on the three dimesnions of community development, namely living standards, education and health. Data were obtained from 336 participants of CSR programs that include students and household members in communities. Results show that the majority of corporations started their CSR in community development in the first decade of the millenium on education-related matters. Recommendations for managing CSR in community development are put forth.